PEMERIKSAAN KANDUNGAN BAHAN KIMIA OBAT (BKO) PREDNISON PADA BEBERAPA SEDIAAN JAMU REMATIK - Ade Wirastuti; A Amaliah Dahlia; Ahmad Najib (Jurnal Fitofarmaka Indonesia, 2016)
A study of identification and assay of prednisone in rheumatic jamu. The aim of this study to identify the presence of Chemicals Drug (CD) in containing prednisone in rheumatic jamu with TLC-densitometry method. Samples extracted with Mesceration method using etanol 96% solvent by sonicator. Qualitative analysis using thin layer chromatography (TLC) with a mobile phase of chloroform : ethyl acetate (1 : 9) indicates that the sample A containing Prednison. Quantitative analysis using a TLC-densitometry at a maximum wave-length 254 nm. The result is one containing prednisone that suspected sample “A” is 475,421 µg/mL and the percentage is 4,754%.